2003
DOI: 10.1002/ajmg.a.20113
|View full text |Cite
|
Sign up to set email alerts
|

What does “A gene for heart disease” mean? A focus group study of public understandings of genetic risk factors

Abstract: There is growing concern in the medical community about potential genetic determinism in the patient population. Limited information about the public understanding of genetic factors in disease formation is available. To access public perceptions of potentially deterministic phrasing of genetic risk factors, we sought to establish interpretations of the phrase, "a gene for heart disease." Focus groups in urban, suburban, and rural communities were conducted from July through October, 2001 in Georgia. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 17 publications
5
51
0
Order By: Relevance
“…There was an almost complete absence of fatalism about the condition, in as much as FH was largely seen as controllable through adhering to appropriate behavioral and therapeutic regimes. Fears that patient populations may understand genetic risk factors for common diseases in a deterministic way [50] appear to be unfounded in the case of FH.…”
Section: Discussionmentioning
confidence: 99%
“…There was an almost complete absence of fatalism about the condition, in as much as FH was largely seen as controllable through adhering to appropriate behavioral and therapeutic regimes. Fears that patient populations may understand genetic risk factors for common diseases in a deterministic way [50] appear to be unfounded in the case of FH.…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts were not corrected for grammar or for formality in order to capture the oral nature of the discussion. Specific questions asked by the moderators have been reported on elsewhere (see, for example, Condit et al, 2002bCondit et al, , 2003Dorgan et al, 2003;Parrott et al, 2003Parrott et al, , 2004Bates et al, 2003;Bevan et al, 2003). In this study, I took a more global view of the data.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Some studies have reported low levels of public understanding of genetic concepts (e.g., location of genes) and applications (e.g., newborn screening), although participants displayed familiarity with genetic terminology (Lanie et al, 2004;Miller, 2004;Catz et al, 2005;Lea et al, 2011). In contrast, other studies have shown some public understanding of genetic concepts and genetics research, such as the meaning of a reported genetic association (Bates et al, 2003;Miller, 2004;Levitt et al, 2005). Longitudinal survey data suggest that awareness and understanding may be increasing (Miller, 2004;Singer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%